The Impact of Digital Marketing, Product Quality, and Customer Relationship Management on Online Shop Consumer Loyalty - Qusairi, Andri Al; Candra, Candra; Sudarta, Sudarta; Iswanto, Dedy; Maniza, Lalu Hendra (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study seeks to explore the effects of digital marketing, product quality, and customer relationship management (CRM) on consumer loyalty within the context of online retail. Employing a quantitative approach, the study conducted a survey among 91 respondents, comprising 34 males and 56 females. Data collection instruments utilized a Likert scale with 29 items designed to measure respondents' perceptions of the study variables. Regression analysis results indicate that collectively, digital marketing, product quality, and CRM explain 49.3% of the variation in consumer loyalty. Specifically, CRM emerges as significantly influential with the highest beta coefficient (0.438) and low statistical significance (p = 0.000), while digital marketing and product quality show less significant impacts With p-values of 0.296 and 0.127, respectively, these results highlight the critical role of effective customer relationship management strategies in fostering consumer loyalty in online commerce. They also indicate the necessity for strategic enhancements in digital marketing and product quality to optimize their influence. This research contributes to the comprehension of the dynamics affecting consumer behavior in the digital age.